A Deep Radio Survey of Hard State and Quiescent Black Hole X-Ray Binaries - Miller-Jones, James; Jonker, P.; Maccarone, T.; Nelemans, G.; Calvelo, D. (Institute of Physics Publishing, Inc, 2011)
We have conducted a deep radio survey of a sample of black hole X-ray binaries in the hard and quiescent states to determine whether any systems were sufficiently bright for astrometric follow-up with high-sensitivity very long baseline interferometric arrays. The one hard-state system, Swift J1753.5–0127, was detected at a level of 0.5 mJy beam–1. All 11 quiescent systems were not detected. In the three cases with the highest predicted quiescent radio brightnesses (GRO J0422+32, XTE J1118+480, and GRO J1655–40), the new capabilities of the Expanded Very Large Array were used to reach noise levels as low as 2.6 µJy beam–1. None of the three sources were detected to 3s upper limits of 8.3, 7.8, and 14.2 µJy beam–1, respectively. These observations represent the most stringent constraints to date on quiescent radio emission from black hole X-ray binaries. The uncertainties in the source distances, quiescent X-ray luminosities at the times of the observations, and the power-law index of the empirical correlation between radio and X-ray luminosities make it impossible to determine whether these three sources are significantly less luminous in the radio band than expected. Thus it is not clear whether that correlation holds all the way down to quiescence for all black hole X-ray binaries.